2004
DOI: 10.1073/pnas.0400185101
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate activates Weibel-Palade body exocytosis

Abstract: Sphingosine 1-phosphate (S1P) not only regulates angiogenesis, vascular permeability and vascular tone, but it also promotes vascular inflammation. However, the molecular basis for the proinflammatory effects of S1P is not understood. We now show that S1P activates endothelial cell exocytosis of Weibel-Palade bodies, releasing vasoactive substances capable of causing vascular thrombosis and inflammation. S1P triggers endothelial exocytosis in part through phospholipase C-␥ signal transduction. However, S1P als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 35 publications
6
32
0
Order By: Relevance
“…Stxbp5 mRNA was expressed in murine tissues, including lung, spleen, and aorta, as measured by quantitative real-time PCR (qPCR; Figure 1B). Stxbp5 mRNA was also found ECs through discrete signaling pathways (37)(38)(39)(40)(41)(42)(43)(44). However, the detailed mechanisms controlling the endothelial SNARE machinery are not fully known.…”
Section: Resultsmentioning
confidence: 99%
“…Stxbp5 mRNA was expressed in murine tissues, including lung, spleen, and aorta, as measured by quantitative real-time PCR (qPCR; Figure 1B). Stxbp5 mRNA was also found ECs through discrete signaling pathways (37)(38)(39)(40)(41)(42)(43)(44). However, the detailed mechanisms controlling the endothelial SNARE machinery are not fully known.…”
Section: Resultsmentioning
confidence: 99%
“…We used dehydro-S1P (dhS1P), a variant of S1P that has only extracellular but not intracellular activity. 26 Treatment of various doses of S1P or dhS1P displayed similar efficacies in stimulating Ang2 exocytosis in ECs ( Figure 3D and supple- mental Figure IV), suggesting that extracellular S1P stimulates Ang2 exocytosis. Extracellular S1P conveys its downstream signaling via plasma membrane GPCR.…”
mentioning
confidence: 88%
“…The sphingolipid S1P is similar to thrombin and histamine in that it can potentiate inflammation in the vasculature via exocytosis of vWF and angiopoietin 2 from WPBs (Matsushita et al, 2004;Jang et al, 2009). Matsushita et al (2004) showed that S1P-mediated exocytosis of WPBs occurs in part via PLCg but also involves extracellular calcium, because both PLC inhibitors and calcium-free media blocked S1P-induced secretion of vWF from human aortic ECs.…”
Section: B Activation Pathways For Exocytosismentioning
confidence: 99%
“…Matsushita et al (2004) showed that S1P-mediated exocytosis of WPBs occurs in part via PLCg but also involves extracellular calcium, because both PLC inhibitors and calcium-free media blocked S1P-induced secretion of vWF from human aortic ECs. Given that the receptor was pertussis toxin sensitive, the authors concluded that the S1P must act via a G i -linked receptor (Matsushita et al, 2004).…”
Section: B Activation Pathways For Exocytosismentioning
confidence: 99%
See 1 more Smart Citation